Ni-based ternary hydrotalcite catalyst as well as preparation method and application thereof
By using Ni-based ternary hydrotalcite catalyst, the composition of Ni, Fe or Co oxides and Ce, Mg or Ti oxides are prepared by hydrothermal method and high-temperature gas phase reduction method, the problem of low reaction activity of the existing catalyst is solved, and the efficient decomposition of ammonia and the stability of the catalyst is improved.
Patent Information
- Application Number
- CN202411723195.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-28
AI Technical Summary
The existing ammonia decomposition catalysts have low reaction activity under normal pressure and extremely low conversion rate, making it difficult to achieve efficient ammonia decomposition.
Ni-based ternary hydrotalcite catalyst is used, composed of oxides of Ni, Fe or Co, oxides of Ce, Mg or Ti, and prepared by hydrothermal method and high-temperature gas phase reduction method to improve nickel dispersion and catalyst stability.
The efficient decomposition of ammonia at lower temperatures is achieved, which improves the ammonia conversion rate and catalyst stability and reduces costs.
Smart Images

Figure CN119701974A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a Ni-based ternary hydrotalcite catalyst and a preparation method and application thereof, belonging to the field of catalysts. Background Art
[0002] As a green and clean energy, hydrogen has high energy density (142MJ kg -1 ) and zero emissions, making it the most ideal alternative to fossil fuels. Promoting the large-scale application of hydrogen energy is of great significance to building a clean, low-carbon, safe and efficient energy system. However, due to the characteristics of hydrogen itself, the large-scale storage and transportation of hydrogen under current conditions still face huge challenges. If the storage and transportation process of hydrogen can be avoided, the cost of hydrogen use will be greatly reduced, promoting the large-scale application of hydrogen energy. Ammonia has the following advantages as a hydrogen storage carrier: 1. Ammonia is easy to liquefy and store (liquefaction pressure is 0.8MPa at 20°C); 2. Ammonia has a high energy density (3000Wh·kg -1 ) and high hydrogen carrying capacity (17.6wt%), which is much higher than methanol and other carbon-based compound fuels and compressed hydrogen; 3. The decomposition products of ammonia are N2 and H2, avoiding CO x The poisoning of Pt electrodes by these substances. And the technology of synthesizing ammonia is very mature and the price of ammonia is low. Therefore, ammonia as a hydrogen carrier, transforming the storage and transportation of hydrogen into the storage and transportation of ammonia, and producing hydrogen by decomposing ammonia have great application prospects.
[0003] The ammonia decomposition reaction to produce hydrogen is shown in formula (1). This reaction is an endothermic reaction with an increase in volume, so increasing the temperature and reducing the pressure are beneficial to the reaction. According to thermodynamic calculations, at normal pressure and a temperature of 400°C, the equilibrium conversion rate of ammonia decomposition can reach 99%. However, from a kinetic point of view, due to the very high activation energy of the reaction, the conversion rate of ammonia decomposition reaction is extremely low under normal pressure and without catalyst catalysis. At normal pressure and without any catalyst, the actual conversion rate of ammonia decomposition reaction at 700°C is less than 10%. Therefore, a highly active catalyst is required to achieve efficient decomposition of ammonia.
[0004] 2NH3 = N2 + 3H2, ΔH = 92.5 kJ mol -1 (1)
[0005] At present, the main ammonia decomposition catalysts include precious metal catalysts (such as Ru, Ir, etc.), non-precious metal catalysts (such as Fe, Co, Ni, Mo, etc.), transition metal carbides and nitrides (such as WC x 、MoN xNi-based catalysts are commonly used in industry, but they face problems such as high reaction temperature and low space velocity. This is mainly due to the poor dispersibility of Ni particles in Ni-based catalysts prepared by conventional precipitation methods, resulting in low reaction activity.
[0006] Hydrotalcite compounds (LDHs) are a new type of inorganic functional materials with a layered structure, and their layered structure is naturally conducive to the dispersion of ions. Ternary hydrotalcite refers to a hydrotalcite system composed of three metal ions. The metal ions themselves have high dispersibility in the hydrotalcite structure, and the metal particles obtained by using this as a precursor to prepare the catalyst also have high dispersibility. In addition, the ternary hydrotalcite composed of the third component such as Ce, Mg, and Ti forms CeO2, MgO, and TiO2 oxides after high-temperature treatment, which can further adjust the structure of the catalyst, thereby improving the dispersibility and anti-sintering ability of the active components. Therefore, the catalyst prepared using the Ni-based ternary hydrotalcite precursor is expected to obtain a highly dispersed and sintering-resistant Ni-based catalyst.
[0007] At present, some patents have been applied for the preparation of ammonia decomposition catalysts. The following are several reported patents for detailed description:
[0008] The Chinese patent 200710119471.4 is publicly named: A method for preparing a supported nickel catalyst for hydrogen production by decomposing ammonia. The patent reports the use of aluminum oxide, silicon oxide or titanium oxide as a carrier and nickel as an active component to prepare a Ni-based catalyst by a precipitation method. The catalyst Ni particles involved in the patent are easy to agglomerate at high temperatures, resulting in low reaction activity.
[0009] The Chinese patent CN 202011067910.3 is publicly named: A catalyst for hydrogen production by decomposition of ammonia, its preparation method and application. The patent reports a Ni-based catalyst prepared by the sol-gel method with a BN rare earth metal oxide composite carrier. However, due to the sol-gel preparation process, some active components will be embedded in the carrier, resulting in the inability of all active components to play a role.
[0010] The Chinese patent CN 202211587775.4 is publicly named: A perovskite catalyst for ammonia decomposition, its preparation method and application. The patent reports that the catalyst carrier is a perovskite oxide, the active component is Ni, and it is used for ammonia decomposition reaction. However, perovskite oxides are difficult to prepare on a large scale and are still far from practical application.
[0011] At present, there is an urgent need to develop an efficient ammonia decomposition catalyst to improve catalyst activity and stability. Summary of the invention
[0012] According to one aspect of the present application, a Ni-based ternary hydrotalcite catalyst is provided, wherein the Ni-based ternary hydrotalcite catalyst is composed of component X, component Y, and component Z;
[0013] The component X is a single substance of Ni, and its mass content in the Ni-based ternary hydrotalcite catalyst is 30-45%;
[0014] The component Y is one of Fe oxide, Co oxide and Mn oxide, and its mass content in the Ni-based ternary hydrotalcite catalyst is 30-45%;
[0015] The component Z is one of Ce oxide, Mg oxide and Ti oxide, and its mass content in the Ni-based ternary hydrotalcite catalyst is 20-35%.
[0016] According to another aspect of the present application, a method for preparing the above-mentioned Ni-based ternary hydrotalcite catalyst is provided, comprising the following steps:
[0017] The aqueous solution A containing component X precursor, component Y precursor and component Z precursor is mixed with aqueous solution B containing alkali, reacted in a reactor, filtered, washed, dried and reduced to obtain the Ni-based ternary hydrotalcite catalyst.
[0018] The component X precursor is selected from at least one of nickel chloride, nickel nitrate and nickel acetate;
[0019] The component Y precursor is selected from at least one of ferric chloride, ferric nitrate, cobalt chloride, cobalt nitrate, manganese nitrate and manganese acetate;
[0020] The component Z precursor is selected from at least one of cerium nitrate, magnesium nitrate and titanium nitrate;
[0021] The base is selected from at least one of urea and sodium bicarbonate;
[0022] The concentration of the aqueous solution A is 0.05-1 mol / L;
[0023] The concentration of the aqueous solution B is 0.5-2 mol / L;
[0024] The volume ratio of the aqueous solution A to the aqueous solution B is 1:1 to 3.
[0025] The reaction temperature is 110-180°C;
[0026] The reaction time is 6 to 24 hours;
[0027] The drying temperature is 60-120°C;
[0028] The drying time is 4 to 12 hours.
[0029] The reduction is a high-temperature gas phase reduction method;
[0030] The reducing atmosphere contains hydrogen and / or ammonia;
[0031] The volume space velocity of the reducing atmosphere is 100-3600h -1 ;
[0032] The reduction temperature is 400-800°C;
[0033] The reduction time is 1 to 48 hours;
[0034] The heating rate of the reduction is 1 to 10°C / min;
[0035] The reduction pressure is normal pressure.
[0036] According to another aspect of the present application, a method for decomposing ammonia is provided, comprising the following steps:
[0037] In a reactor, ammonia gas is contacted with a catalyst to undergo a decomposition reaction to produce hydrogen gas and nitrogen gas;
[0038] The catalyst is the above-mentioned Ni-based ternary hydrotalcite catalyst.
[0039] The space velocity of the ammonia gas is 200 to 60000 ml / g·h.
[0040] The temperature of the decomposition reaction is 400-900°C.
[0041] Optionally, the temperature of the decomposition reaction is 500-700°C.
[0042] The beneficial effects of this application include:
[0043] 1) The ammonia decomposition catalyst provided in the present application can achieve efficient decomposition of ammonia at a relatively low temperature.
[0044] 2) The ammonia decomposition catalyst provided in the present application has high nickel dispersibility and high stability.
[0045] 3) The nickel-based ammonia decomposition catalyst provided in the present application, as well as its preparation method and application, have the advantages of low ammonia decomposition reaction temperature, high ammonia space velocity, high ammonia conversion rate and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The stability curves of the catalysts of Example 1 and Comparative Example 1 in the ammonia decomposition reaction. DETAILED DESCRIPTION
[0047] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0048] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0049] Example 1
[0050] 1) Preparation of Ni-based ternary hydrotalcite matrix.
[0051] Weigh 7.43g Ni(NO3)2·6H2O, 9.88g Co(NO3)2·6H2O and 2.85g Ce(NO3)3, and dissolve them in 100ml deionized water to make solution A. Take 6g urea and dissolve it in 100ml deionized water to make solution B. Mix solution A and solution B and add them to a 500ml hydrothermal kettle. Place the reactor in a 150℃ drying oven to react for 12h. Then filter and wash to neutrality, put it in an 80℃ oven and dry it for 12h to obtain a Ni-based ternary hydrotalcite matrix, which is recorded as NiCoCe-LDH sample.
[0052] 2) Preparation of XYZ catalyst.
[0053] Weigh 2 g of the prepared NiCoCe-LDH sample and reduce it with hydrogen at a temperature of 600 °C. The heating rate from room temperature to the reduction temperature is 5 °C / min and the volumetric space velocity of hydrogen is 1000 h -1 , the pressure was normal pressure, and the reduction time was 12 h. The catalyst was obtained and was recorded as NiCoCe-LDH.
[0054] The reaction conditions for the catalyst decomposition with ammonia were: ammonia concentration of 99.9%, fixed bed reactor, reaction temperature of 500°C to 700°C, and space velocities of 200, 1000, 30000, and 60000 ml / g·h, respectively. The reaction results are shown in Table 1.
[0055] Example 2
[0056] 1) Preparation of Ni-based ternary hydrotalcite matrix.
[0057] Weigh 6.07g NiCl2·6H2O, 8.07g CoCl2·6H2O and 5.52g Mg(NO3)2, and dissolve them in 100ml deionized water to make solution A. Take 12g urea and dissolve it in 100ml deionized water to make solution B. Mix solution A and solution B and add them to a 500ml hydrothermal kettle. Place the reactor in a 180℃ drying oven to react for 6h. Then filter and wash to neutrality, put it in a 120℃ oven and dry it for 4h to obtain a Ni-based ternary hydrotalcite matrix, which is recorded as NiCoMg-LDH sample.
[0058] 2) Preparation of XYZ catalyst.
[0059] Weigh 2 g of the prepared NiCoMg-LDH sample and reduce it with ammonia at 800 °C. The heating rate from room temperature to the reduction temperature is 1 °C / min and the volumetric space velocity of hydrogen is 100 h -1 , the pressure was normal pressure, and the reduction time was 48 h. The catalyst was obtained and was recorded as NiCoMg-LDH.
[0060] The reaction conditions for the catalyst decomposition with ammonia were: ammonia concentration of 99.9%, fixed bed reactor, reaction temperature of 500°C to 700°C, and space velocity of 30,000 ml / g·h. The reaction results are shown in Table 1.
[0061] Example 3
[0062] 1) Preparation of Ni-based ternary hydrotalcite matrix.
[0063] Weigh 6.36g Ni(CH3COO)2·4H2O, 9.88g Co(NO3)2·6H2O and 3.56g TiCl4, and dissolve them in 100ml deionized water to make solution A. Take 6g urea and dissolve it in 200ml deionized water to make solution B. Mix solution A and solution B and add them to a 500ml hydrothermal kettle. Place the reactor in a 110℃ drying oven to react for 24h. Then filter and wash to neutrality, put it in a 60℃ oven and dry it for 12h to obtain a Ni-based ternary hydrotalcite matrix, which is recorded as NiCoTi-LDH sample.
[0064] 2) Preparation of XYZ catalyst.
[0065] Weigh 2g of the prepared NiCoTi-LDH sample and reduce it with a mixture of 50% ammonia and 50% hydrogen at a temperature of 700°C. The heating rate from room temperature to the reduction temperature is 10°C / min and the volumetric space velocity of hydrogen is 3600h-1. -1 , the pressure was normal pressure, and the reduction time was 1 h. The catalyst was obtained and was recorded as NiCoTi-LDH.
[0066] The reaction conditions for the catalyst decomposition with ammonia were: ammonia concentration of 99.9%, fixed bed reactor, reaction temperature of 500°C to 700°C, and space velocity of 30,000 ml / g·h. The reaction results are shown in Table 1.
[0067] Example 4
[0068] 1) Preparation of Ni-based ternary hydrotalcite matrix.
[0069] Weigh 11.15g Ni(NO3)2·6H2O, 10.85g Fe(NO3)3·9H2O and 2.37g Ce(NO3)3 and dissolve them in 100ml deionized water to make solution A. Take 6g urea and dissolve it in 100ml deionized water to make solution B. Mix solution A and solution B and add them to a 500ml hydrothermal kettle. Place the reactor in a 120℃ drying oven to react for 12h. Then filter and wash to neutrality, put it in a 110℃ oven and dry it for 6h to obtain a Ni-based ternary hydrotalcite matrix, which is recorded as NiFeCe-LDH sample.
[0070] 2) Preparation of XYZ catalyst.
[0071] Weigh 2 g of the prepared NiFeCe-LDH sample and reduce it with hydrogen at a temperature of 400 °C. The heating rate from room temperature to the reduction temperature is 5 °C / min and the volumetric space velocity of hydrogen is 2000 h -1 , the pressure was normal pressure, and the reduction time was 48 h. The catalyst was obtained and was recorded as NiFeCe-LDH.
[0072] The reaction conditions for the catalyst decomposition with ammonia were: ammonia concentration of 99.9%, fixed bed reactor, reaction temperature of 500°C to 700°C, and space velocity of 30,000 ml / g·h. The reaction results are shown in Table 1.
[0073] Example 5
[0074] 1) Preparation of Ni-based ternary hydrotalcite matrix.
[0075] Weigh 8.67g Ni(NO3)2·6H2O, 7.33g Mn(NO3)2 and 1.9g Ce(NO3)3 and dissolve them in 100ml deionized water to make solution A. Take 10g urea and dissolve it in 100ml deionized water to make solution B. Mix solution A and solution B and add them to a 500ml hydrothermal kettle. Place the reactor in a 120℃ drying oven to react for 12h. Then filter and wash to neutrality, put it in an 80℃ oven and dry it for 8h to obtain a Ni-based ternary hydrotalcite matrix, which is recorded as NiMnCe-LDH sample.
[0076] 2) Preparation of XYZ catalyst.
[0077] Weigh 2 g of the prepared NiMnCe-LDH sample and reduce it with hydrogen at a temperature of 600 °C. The heating rate from room temperature to the reduction temperature is 5 °C / min and the volumetric space velocity of hydrogen is 2000 h -1 , the pressure was normal pressure, and the reduction time was 12 h. The catalyst was obtained and was recorded as NiMnCe-LDH.
[0078] The reaction conditions for the catalyst decomposition with ammonia were: ammonia concentration of 99.9%, fixed bed reactor, reaction temperature of 500°C to 700°C, and space velocity of 30,000 ml / g·h. The reaction results are shown in Table 1.
[0079] Example 6
[0080] 1) Preparation of Ni-based ternary hydrotalcite matrix.
[0081] Weigh 8.67g Ni(NO3)2·6H2O, 7.27g FeCl3·6H2O and 6.44g Mg(NO3)2 and dissolve them in 100ml deionized water to make solution A. Take 12g urea and dissolve it in 100ml deionized water to make solution B. Mix solution A and solution B and add them to a 500ml hydrothermal kettle. Place the reactor in a 150℃ drying oven to react for 12h. Then filter and wash to neutrality, put it in an 80℃ oven and dry it for 8h to obtain a Ni-based ternary hydrotalcite matrix, which is recorded as NiFeMg-LDH sample.
[0082] 2) Preparation of XYZ catalyst.
[0083] Weigh 2 g of the prepared NiFeMg-LDH sample and reduce it with hydrogen at a temperature of 500 °C. The heating rate from room temperature to the reduction temperature is 5 °C / min and the volumetric space velocity of hydrogen is 2000 h -1 , the pressure was normal pressure, and the reduction time was 12 h. The catalyst was obtained and was recorded as NiFeMg-LDH.
[0084] The reaction conditions for the catalyst decomposition with ammonia were: ammonia concentration of 99.9%, fixed bed reactor, reaction temperature of 500°C to 700°C, and space velocity of 30,000 ml / g·h. The reaction results are shown in Table 1.
[0085] Example 7
[0086] 1) Preparation of Ni-based ternary hydrotalcite matrix.
[0087] Weigh 9.91g Ni(NO3)2·6H2O, 6.3g (CH3COO)2Mn and 2.37g TiCl4 and dissolve them in 100ml deionized water to make solution A. Take 16.8g sodium bicarbonate and dissolve it in 100ml deionized water to make solution B. Mix solution A and solution B and add them to a 500ml hydrothermal kettle. Place the reactor in a 150℃ drying oven to react for 12h. Then filter and wash to neutrality, put it in an 80℃ oven and dry it for 8h to obtain a Ni-based ternary hydrotalcite matrix, which is recorded as NiMnTi-LDH sample.
[0088] 2) Preparation of XYZ catalyst.
[0089] Weigh 2 g of the prepared NiMnTi-LDH sample and reduce it with hydrogen at a temperature of 500 °C. The heating rate from room temperature to the reduction temperature is 5 °C / min and the volumetric space velocity of hydrogen is 2000 h -1 , the pressure was normal pressure, and the reduction time was 12 h. The catalyst was obtained and recorded as NiMnTi-LDH sample.
[0090] The reaction conditions for the catalyst decomposition with ammonia were: ammonia concentration of 99.9%, fixed bed reactor, reaction temperature of 500°C to 700°C, and space velocity of 30,000 ml / g·h. The reaction results are shown in Table 1.
[0091] Comparative Example 1
[0092] 1) Preparation of Ni-based binary hydrotalcite matrix.
[0093] Weigh 7.43g Ni(NO3)2·6H2O and 9.88g Co(NO3)2·6H2O, and dissolve them in 100ml deionized water to make solution A. Take 6g urea and dissolve it in 100ml deionized water to make solution B. Mix solution A and solution B and add them to a 500ml hydrothermal kettle. Place the reactor in a 150℃ drying oven to react for 12h. Then filter and wash to neutrality, put it in an 80℃ oven and dry it for 12h to obtain a Ni-based binary hydrotalcite matrix, which is recorded as NiCo-LDH sample.
[0094] 2) Preparation of XY catalyst.
[0095] Weigh 2 g of the prepared NiCo-LDH sample and reduce it with hydrogen at a temperature of 600 °C. The heating rate from room temperature to the reduction temperature is 5 °C / min and the volumetric space velocity of hydrogen is 1000 h -1 , the pressure was normal pressure, and the reduction time was 12 h. The catalyst was obtained and was recorded as NiCo-LDH.
[0096] The reaction conditions for the catalyst decomposition with ammonia were: ammonia concentration of 99.9%, fixed bed reactor, reaction temperature of 500°C to 700°C, and space velocity of 30,000 ml / g·h. The reaction results are shown in Table 1.
[0097] Comparative Example 2
[0098] Weigh 1.0g CeO2 carrier, weigh 0.6226g NiNO3 and dissolve it in 2g deionized water to make a mixed solution, add it dropwise to the CeO2 carrier and mix it evenly. Soak at room temperature for 12h, dry at 80℃ for 12h, and calcine at 300℃ in air atmosphere for 4h, where the Ni mass content is 20%. Then, it is reduced with hydrogen at a temperature of 600℃, a heating rate of 5℃ / min from room temperature to the reduction temperature, and a hydrogen volume space velocity of 2000h -1 , the pressure was normal pressure, and the reduction time was 1 h. The catalyst was obtained and was recorded as 20% Ni / CeO2.
[0099] The reaction conditions for the catalyst decomposition with ammonia are: ammonia concentration of 99.9%, fixed bed reactor, reaction temperature of 500°C to 700°C, and space velocity of 30000 ml / g·h. The reaction results are shown in Table 1. Example Result Analysis:
[0100] From the data analysis in Table 1, it can be seen that the XYZ-LDH catalyst prepared with a Ni-based ternary hydrotalcite precursor has good activity in the ammonia decomposition reaction. For the NiCoCe-LDH catalyst, an ammonia conversion rate of >99% can be achieved at 700°C. Efficient conversion of ammonia at high space velocity can be achieved at 700°C and 30,000 ml / g·h. However, the catalyst prepared with a Ni-based binary hydrotalcite precursor in Comparative Example 1 has a conversion rate of only 68.90% at 700°C and 30,000 ml / g·h. This shows that the catalyst prepared with a Ni-based ternary hydrotalcite precursor has higher activity. Since CeO2 oxide can further adjust the structure of the catalyst, thereby improving the dispersibility of the active component. In addition, by Figure 1 It can be seen that the catalyst prepared using the ternary hydrotalcite precursor also exhibits higher resistance to sintering and has higher stability in the ammonia decomposition reaction.
[0101] Table 1 Reaction performance of ammonia decomposition on different catalysts
[0102]
[0103]
[0104] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A Ni-based ternary hydrotalcite catalyst, characterized in that: The Ni-based ternary hydrotalcite catalyst consists of component X, component Y and component Z; The component X is a single substance of Ni, and its mass content in the Ni-based ternary hydrotalcite catalyst is 30-45%; The component Y is one of Fe oxide, Co oxide and Mn oxide, and its mass content in the Ni-based ternary hydrotalcite catalyst is 30-45%; The component Z is one of Ce oxide, Mg oxide and Ti oxide, and its mass content in the Ni-based ternary hydrotalcite catalyst is 20-35%.
2. A method for preparing the Ni-based ternary hydrotalcite catalyst according to claim 1, characterized in that: The following steps are involved: The aqueous solution A containing component X precursor, component Y precursor and component Z precursor is mixed with aqueous solution B containing alkali, reacted in a reactor, filtered, washed, dried and reduced to obtain the Ni-based ternary hydrotalcite catalyst.
3. The preparation method according to claim 2, characterized in that: The component X precursor is selected from at least one of nickel chloride, nickel nitrate and nickel acetate; The component Y precursor is selected from at least one of ferric chloride, ferric nitrate, cobalt chloride, cobalt nitrate, manganese nitrate and manganese acetate; The component Z precursor is selected from at least one of cerium nitrate, magnesium nitrate and titanium nitrate; The alkali is selected from at least one of urea and sodium bicarbonate.
4. The preparation method according to claim 2, characterized in that: The concentration of the aqueous solution A is 0.05-1 mol / L; The concentration of the aqueous solution B is 0.5-2 mol / L; The volume ratio of the aqueous solution A to the aqueous solution B is 1:1-3.
5. The preparation method according to claim 2, characterized in that: The reaction temperature is 110-180°C; The reaction time is 6 to 24 hours; The drying temperature is 60-120°C; The drying time is 4 to 12 hours.
6. The preparation method according to claim 2, characterized in that: The reduction is a high-temperature gas phase reduction method; The reducing atmosphere contains hydrogen and / or ammonia; The volume space velocity of the reducing atmosphere is 100-3600h -1 ; The reduction temperature is 400-800°C; The reduction time is 1 to 48 hours; The heating rate of the reduction is 1 to 10°C / min; The reduction pressure is normal pressure.
7. A method for decomposing ammonia, characterized in that: The following steps are involved: In a reactor, ammonia is contacted with a catalyst to undergo a decomposition reaction to obtain hydrogen and nitrogen; the catalyst is the Ni-based ternary hydrotalcite catalyst as claimed in claim 1.
8. The method according to claim 7, characterized in that The space velocity of the ammonia gas is 200 to 60000 ml / g·h.
9. The method according to claim 7, characterized in that: The temperature of the decomposition reaction is 400-900°C.
10. The method according to claim 7, characterized in that The temperature of the decomposition reaction is 500-700°C.
Citation Information
Patent Citations
Supported type nickel catalyst for producing hydrogen from decomposition of ammonia and preparation method
CN101352685A
A catalyst for hydrogen production from ammonia decomposition, its preparation method and application
CN112337494B
Ru-based catalyst for hydrogen production through ammonia decomposition as well as preparation and application methods of Ru-based catalyst
CN115920942A